RESPONS PSIKOLOGIS REMAJA KORBAN CYBERBULLYING: STUDI KASUS PADA REMAJA - Roland Lekatompessy; Nur Setiawati Dewi; Megah Andriany (Jurnal Surya Muda, 2022)
Cyberbullying has became a world concern, because many countries in the world has experienced about cyberbullying including Indonesia especially Ambon City. Cyberbullying is very important to overcome, because cyberbullying has a very serious impact on adolescent, such as depression and suicide. This study to explore the psychological response of adolescents as a cyberbullying victims is very limited. This research is a qualitative with an interpretative phenomenology design. The sample in this study were 3 adolescence of Ambon City as informants, and has inclusion criteria such as age 10-19 years, use social media, have both Ambonese parents,and also well communicate. This study has used purposive sampling for sampling, and data collection has used indepth interview. Processing and data analysis has used Interpretative Phenomenological Analysis (IPA). The results obtained 3 themes that describe psyvhologycal response of adolescence as a cyberbullying victims, the three theme are shame, hurt, and hopelessness. Adolescent experience as cyberbullying has affect the mood and made adolescent not enthusiastic in living life. Prevention programs in every levels of nursing need to be carried out in to preventing adolescent cyberbullying, and also to handling the impact that occurs on adolescent cyberbullying victims.